TERAPI INABAH DAN PECANDU - Moh Toriqul Chaer (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2014)
This study aims to determine the therapeutic application in Inabah VII and Anak Bina's views on the therapeutic process in Inabah. This study specifically focuses on ethnographers working model using a phenomenological approach. The data is generated through in-depth interviews, participant observation, library research, documentation, and active listening. The results of this study indicate that, first, Anak Bina in Inabah VII are healed through several stages including mandi Taubat, prayer therapy, therapy TQN dzikir, fasting, khataman and manaqiban; second, Anak Bina have their own perspectives on the therapy they are experiencing. Generally, the views of Anak Bina to therapy Inabah can be divided into three stages: denial, acceptance and habituation.